Alcohol dysregulates corticotropin-releasing-hormone (CRH) promoter activity by interfering with the negative glucocorticoid response element (nGRE). - Magdalena M Przybycien-Szymanska; Natasha N Mott; Toni R Pak (PLoS ONE, 2011)
EtOH exposure in male rats increases corticotropin-releasing hormone (CRH) mRNA in the paraventricular nucleus of the hypothalamus (PVN), a brain region responsible for coordinating stress and anxiety responses. In this study we identified the molecular mechanisms involved in mediating these effects by examining the direct effects of EtOH on CRH promoter activity in a neuronal cell line derived from the PVN (IVB). In addition, we investigated the potential interactions of EtOH and glucocorticoids on the CRH promoter by concomitantly treating cells with EtOH and the glucocorticoid receptor (GR) antagonist RU486, and by sequentially deleting GR binding sites within glucocorticoid response element (GRE) on the CRH promoter. Cells were transiently transfected with a firefly luciferase reporter construct containing 2.5 kb of the rat wild type (WT) or mutated CRH promoter. Our results showed that EtOH treatment induced a biphasic response in CRH promoter activity. EtOH exposure for 0.5 h significantly decreased promoter activity compared to vehicle treated controls, whereas promoter activity was significantly increased after 2.0 h of EtOH exposure. Treatment with RU486, or deletion of the GR binding sites 1 and 2 within the GRE, abolished the EtOH-induced increase in the promoter activity, however did not affect EtOH-induced decrease in CRH promoter activity at an earlier time point. Overall, our data suggest that alcohol exposure directly regulates CRH promoter activity by interfering with the normal feedback mechanisms of glucocorticoids mediated by GR signaling at the GRE site of the CRH promoter.